Antimicrobial behavior, low-stress mechanical properties, and comfort of knitted fabrics made from poly (hydroxybutyrate-co-hydroxyvalerate)/polylactide acid filaments and cotton yarns. Issue 1 (January 2022) - Liu, Shirui; Ma, Linlin; Ding, Xujiao; Wong, Kelly C; Tao, Xiao-Ming
This article presents a systematic investigation of the knitted fabrics made from various blends of intrinsically antimicrobial poly (hydroxybutyrate-co-hydroxyvalerate)/polylactide acid filaments and cotton staple fibers. The effects of blend yarn, fabric structures, and distributions of fibers on antimicrobial properties of resultant yarns and knitted fabrics were studied. The relationships among fiber distribution, blend ratio, and anti-microbial properties were experimentally determined for three blend yarns made by sirofil, wrap-spun, and core-spun spinning technologies. The fabrics made from the sirofil-spun and wrap-spun yarns show better anti-microbial effects against Staphylococcus aureus, Klebsiella pneumoniae, and Candida albicans than those of the core-spun yarns, according to the standard AATCC100-2012 Antibacterial Finishes on Textile Materials (American Association of Textile Chemists and Colorists, 2012). An alternative blending method of co-knitting of the pure poly (hydroxybutyrate-co-hydroxyvalerate)/polylactide acid yarns and cotton yarns achieved excellent antimicrobial effects. Furthermore, a wearing trial of underwear made from the blended knitted fabrics was conducted in a nursing home. The wearing comfort of the garments, low-stress mechanical and surface properties of fabrics were evaluated objectively by the Kawabata Evaluation System of Fabric (KESF) system and subjectively by a questionnaire survey to users.